Pendayagunaan Kawasan Bantaran Rel Kereta Api dan Jembatan Layang Untuk Sarana Publik Kota Medan: Pendayagunaan Kawasan Bantaran Rel Kereta Api dan Jembatan Layang Untuk Sarana Publik Kota Medan - Zulkifli, Zulkilfli Siregar; Lubis, Sudirman; ., Andri (Talenta Publisher, 2022)
This research was conducted in the underpass of the flyover in the Ampera Medan road corridor. The purpose and objective is to provide scientific concepts related to the spatial arrangement under flyovers that are not currently well managed and tend to cause acts of vandalism in the space. The construction of flying cross-construction in several plot areas is generally a new open open space linearly. underneath. Thus the space under the flyover which was initially unproductive will become a point of interest for the surrounding environment. Furthermore, a well-organized space and area will certainly generate economic growth through the support of a well-planned and correct management system. Based on a spatial analysis that is adapted to the function of public space, good planning and management is needed to support and maintain the continuity of activities through creativity and interesting information for the public in public spaces under the Ampera Medan railway flyover. The arrangement of open areas located in flyover and railway areas often creates contradictions and social problems that are quite crucial, especially related to state-owned land ownership. The open space under the Ampera Medan road overpass is currently a lost area (unproductive land) and an act of vandalism that contains immoral messages. The arrangement of open spaces located on the railway underpass as a public space will provide a positive image for the area and become an attractive place for the city of Medan with the availability of jogging tracks as a sports venue, performance arena and social interaction space for the community